The EPA Conventional Reduced Risk Pesticide Program - Frederick M. Fishel (EDIS)
The Food Quality Protection Act (FQPA) of 1996 initiated the U.S. Environmental Protection Agency’s (EPA) Conventional Reduced Risk Pesticide Program. Its purpose is to expedite the review and registration process of conventional pesticides that pose less risk to human health and the environment than existing conventional alternatives. Riskier conventional alternatives are those pesticides EPA deems as having neurotoxic, carcinogenic, reproductive, and developmental toxicity, or groundwater contamination effects. It serves as a means to ensure that reduced risk pesticides enter the channels of trade and are available to growers as soon as possible. This 11-page fact sheet was written by F.M. Fishel, and published by the UF Department of Agronomy, April 2013.